Benefit of self-managed anticoagulation in patients with left ventricular assist device - Vogeler, Elisa Johanna; Dieterlen, Maja-Theresa; Garbade, Jens; Lehmann, Sven; Jawad, Khalil M.; Borger, Michael A.; Meyer, Anna L. (The thoracic and cardiovascular surgeon, 2021)
Background The exact monitoring of the therapeutic-range international normalized ratio (INR) after left ventricular assist device (LVAD) implantation is an important aim to reduce the risk of thrombosis or bleeding complications. Service providers offer a telemedical anticoagulation service (CS). Methods We compared LVAD patients using the CS (n = 15) to those who received regular medical care (RMC; n = 15) to investigate if telemedicine supervision increased the INR-specific time in the therapeutic range (TTR) during anticoagulation. All patients received self-management training for phenprocoumon medication according to their INR value. INR values were documented for 12 months. A survey (scale: 1 = not satisfied and 10 = very satisfied) was used to determine patient's satisfaction and psychological well-being. Results A total of 1,798 INR measurements were analyzed. The TTRRosendaal was higher in patients undergoing RMC (78.1 ± 14.3%) compared with that in patients using the CS (58.3 ± 28.0%, p = 0.03). The patient's satisfaction with the coagulation setting at the beginning of the study (RMC: 6.7 ± 3.1, CS: 7.2 ± 3.0, p = 0.74) and psychological wellbeing (RMC: 6.5 ± 1.9, CS: 6.5 ± 2.7, p = 0.97) were comparable between both groups. Conclusion We found that INR self-management is superior regarding the efficiency of post-LVAD anticoagulation therapy when compared with telemedical (CS)-based INR management in a small study cohort. Intensive training by experienced staff was able to replace CS.